Cryoablation of Anteroseptal Accessory Pathways with a His Bundle Electrogram on the Ablation Catheter - Liberman, Leonardo (Indian Pacing Electrophysiol J, 2014)
BACKGROUND: Radiofrequency catheter ablations of anteroseptal (AS) accessory pathways (AP) in pediatric patients have higher incidence of atrioventricular (AV) block than other AP locations. We report our experience using cryoablation in pediatric patients where a His bundle electrogram was noted on the ablation catheter at the site of the successful ablation. METHODS AND RESULTS: We retrospectively reviewed all patients ≤21 years that underwent cryoablation for an AS AP from 2005 to 2012 at our institution (n=70). Patients with a His bundle electrogram noted on the cryoablation catheter at the location of the successful lesion were identified (n=6, 8.5%). All six patients had ventricular preexcitation. Median age of 15.9 years (7.2 - 18.2). AV nodal function was monitored during the cryoablation with intermittent rapid atrial pacing conducted through the AV node (n=2), with atrial extra-stimulus testing (n=2), or during orthodromic reentrant tachycardia (n=2). Acute success occurred in all patients. Two patients had early recurrence of AP conduction. Both patients underwent a second successful cryoablation, again with a His bundle electrogram on the cryoablation catheter. At a median follow-up of 13 months (3 to 37 months) there was no recurrence of accessory pathway conduction and AVN function was normal. CONCLUSION: In a small number of pediatric patients with AS AP with a His bundle electrogram seen on the ablation catheter, the use of cryotherapy was safe and effective for elimination of AP conduction without impairment of AV nodal conduction.